RESILIENCE AND ADAPTABILITY OF TEACHERS AND STUDENTS DURING THE WAR IN UKRAINE - Victorija V. Zhelanova; Inna V. Leontieva; Svitlana P. Palamar; Victoriia I. Dmytrenko; Kateryna A. Brovko; Dmytro V. Zhelanov; Borys I. Palamar (Клінічна та профілактична медицина, 2025)
Introduction. The article presents the logic and results of the study on the resilience and adaptability of teachers and students in wartime conditions by determining the theoretical and methodological foundations of the study, developing a criterion apparatus and diagnostic tools, and conducting an experimental study within the framework of cooperation with the Luhansk Taras Shevchenko National University, Borys Grinchenko Kyiv Metropolitan University, and Bogomolets National Medical University.